The Relationship Between Pre-Operative Glycosylated Haemoglobin and Opioid Consumption After Caesarean Section in Women With Gestational Diabetes Mellitus - Yang, Chen; Li, Yue; Hu, Jianying; Wu, Jiangnan; Huang, Shaoqiang (Frontiers in Endocrinology, 2022)
Introduction: Women with Gestational diabetes mellitus (GDM) had a higher need and consumption of analgesics than women without GDM. The preoperative level of HbA1c was associated with the postoperative consumption for analgesics in diabetic patients. This prospective observational study go further to investigate the relationship between the pre-operative HbA1c and the post-operative consumption for analgesics in women with GDM. Methods: Women with GDM and a singleton pregnancy undergoing elective cesarean section under combined spinal-epidural anaesthesia were divided into two groups based on pre-operative HbA1c: the normal group (HbA1c < 6%) and the abnormal group (HbA1c ≥ 6%). Analgesics consumption, number of patient-controlled analgesia (PCA) compression, and pain scores in 6 hours and 24 hours post-operation were compared between the two groups. Then Pearson's correlation coefficient and a stepwise multivariate linear regression were performed to investigate possible independentpredictors of post-operative 24-hour sufentanil consumption. Results: Analgesics consumption was significantly lower (18.8 ± 0.4 vs 23.2 ± 4.3; 82.7 ± 2.4 vs 115.8 ± 17.4, P < 0.001),and number of PCA compressions was significantly less frequent (1 [1-2] vs 3 [1-5]; 5 [3-7] vs 7 [3-15], P < 0.001), and in the normal group than in the abnormal group in 6 hours and 24 hours post-operation.The univariate analysis showed that sufentanil consumption at 24 hours post-operation was significantly related to pre-operative HbA1c (r = 0.338, P < 0.001) and parity (r = 0.184, P = 0.03) and was related to blood glucose management methods (r = 0.172, P = 0.043). Multivariate linear regression analysis showed that HbA1c was the independent factor related to post-operative 24-hour sufentanil consumption (adjusted r2 = 0.246, P < 0.001) Conclusions: This study demonstrated that in pregnant women with GDM, the pre-operative HbA1c is independently related to the need for and consumption of analgesics in 24 hours after CS.